'A modern chamber of horrors'? Temporary Holocaust exhibitions as sites of memory: the 1961 Warsaw Ghetto commemoration exhibition, Melbourne. Issue 4 (2nd October 2018) - Cooke, Steven
ABSTRACT: This paper examines the 1961 Warsaw Ghetto exhibition in Melbourne, Australia. Within the context of Eichmann's trial in Israel and fears of rising anti-Semitism in Australia, the exhibition is a site through which debates over Jewish identity, Holocaust memory, and the hitherto marginalised role of temporary exhibitions can be understood. Using archival traces, the paper examines the intentions of the exhibition's organisers, and its reception by visitors. It shows how representations of the Holocaust were shaped by local concerns, the availability of information from emerging global networks of memorial institutions, and the evolving category of 'survivor'. It adds to a nuanced reading of Holocaust memorial forms, unsettling established narratives of Holocaust memory in Australia.